Sharing the Island: Economic and social challenges and opportunities: Evidence from an ESRI research programme - McGinnity, Frances; Bergin, Adele; McGuinness, Seamus; Smyth, Emer (ESRI, 2025)
Ireland and Northern Ireland share many social, historical and geographical characteristics but their political institutions and the configuration of policy are very different. This report summarises some key findings from the extensive and ambitious research programme between the ESRI and the Shared Island Unit (SIU) of the Department of the Taoiseach over the past four years, with 15 research reports published in total. The focus of the joint research programme has been broadly to investigate the economic and social challenges and opportunities that sharing the island presents. The purpose of this overview report is to synthesise some key findings from the programme reports and bring out interlinkages between them, as well as to highlight and reflect on implications for policy learning for the island in the future.
Keywords: Northern Ireland, Ireland; Labour Markets and Skills